Ground‐Based Observations of VLF Waves as a Proxy for Satellite Observations: Development of Models Including the Influence of Solar Illumination and Geomagnetic Disturbance Levels. Issue 4 (15th April 2019) - Simms, Laura E.; Engebretson, Mark J.; Clilverd, Mark A.; Rodger, Craig J.
Abstract: Ground observations of VLF (very low frequency) waves have often been used to infer VLF activity in the magnetosphere; however, they are not an unbiased measure of activity at satellite altitudes due to transionospheric absorption and subionospheric attenuation. We propose several empirical models that control for these effects. VLF power spectral density (PSD) from the VLF/ELF Logger Experiment (VELOX, L=4.6, Halley, Antarctica) is used to predict DEMETER low Earth orbit VLF PSD. Validation correlations of these models are as high as 0.764; thus, ground VLF receivers spaced around the Earth could provide coverage of outer radiation belt lower band chorus over the latitudinal limits of this model (±45–75°). Correlations of four frequency bands (centered at 0.5, 1.0, 2.0, and 4.25 kHz) are compared. The simple linear correlation between ground and satellite VLF PSD in the 1.0‐kHz channel was 0.606 (at dawn). A cubic model resulted in higher correlation (0.638). VLF penetration to the ground is reduced by ionospheric absorption during solar illumination and by disruption of ducting field lines during disturbed conditions. Subionospheric attenuation also reduces VLF observations from distant field lines. Addition of these covariates improved predictions. Both solar illumination and disturbed conditions reduced ground observation of VLF PSD, with higher power waves penetrating to the ground proportionately less than lower power waves. The effect of illumination in reducing wave penetration was more pronounced at higher frequency (4.25 kHz), with the effect at a midrange frequency (2.0 kHz) falling between these two extremes. Key Points: Models accounting for transionospheric absorption and subionospheric attenuation improve satellite‐ground VLF PSD correlations Validation of these empirical models resulted in correlations between predicted and observed satellite VLF PSD of up to 0.764 Ground VLF receivers spaced around the Earth could provide longitudinal coverage of outer radiation belt chorus over ±45–75° latitude